Caterpillars that Defoliate Trees and Shrubs - Eileen A. Buss; Albert E. Mayfield (EDIS)
ENY-353, a 5-page illustrated fact sheet by Eileen A. Buss and Albert E. Mayfield, provides information about damage, identification and biology, monitoring and management of caterpillars. Includes links to additional information and tables of insecticides registered in Florida for use against caterpillars, for homeowners and professional use. Published by the UF Entomology and Nematology Department, June, 2006.